Moving from command and control to flexible use and to a spectrum commons - Rohit Prasad; V. Sridhar (International Telecommunications Society (ITS), 2013)
In most countries, the command and control approach is usually the starting point of the liberalization of the telecommunications industry, which had previously been entirely in the public sector. The command and control approach is useful for achieving early roll-out and rapid growth. However, there are attendant risks of regulatory failures including spectrum getting 'stuck' in lower value uses, and absence of mechanisms to put under-utilized spectrum to a better use. The command and control regime begins to fail in the face of several new developments including the maturation of competition, development of new technologies in pre-existing bands. Moving to a hybrid model of flexible spectrum use and spectrum commons is the need of the hour. The transition to the new model cannot be made in a single stroke since the elements of the C&C framework are inter-linked and bound together by an inherent logic. For instance moving to spectrum auctions requires the dismantling of ascending spectrum usage charges, but political pressure may require that the move be revenue-neutral. This paper highlights aspects of a phased approach to arriving at the new paradigm of spectrum management.
Keywords: 330